Delphi Consensus on Clinical Applications of GOLD 2023 Recommendations in COPD Management: How Aligned are Recommendations with Clinical Practice? - Anzueto, Antonio; Cohen, Mark; Echazarreta, Andres L.; Elassal, Gehan; Godoy, Irma [UNESP]; Paramo, Rafael; Sayiner, Abdullah; Torres-Duque, Carlos A.; Acharya, Sudeep; Aggarwal, Bhumika; Erkus, Hakan; Levy, Gur (Springer Nature, 2024)
The goal of this Delphi study was to understand and assess the level of alignment among the respiratory experts on the application of key changes and recommendations proposed by the GOLD 2023 report in their routine clinical practice for the management of patients with chronic obstructive pulmonary disease (COPD). There were two online surveys in this study, and experts from 16 countries (primarily focused on developing countries) were invited to participate. Using the Delphi method, expert representatives shared their insights with the aim of optimizing patient care. The alignment was assessed in six well-defined themes: 1) Overall view on GOLD/other recommendations; 2) Assessing patients with COPD; 3) Initial pharmacological treatment in patients with COPD; 4) Vaccination for patients with COPD; 5) Follow-up pharmacological treatment in patients with COPD; and 6) Survival evidence in patients with COPD. Participants expressed a high level of agreement regarding key concepts of the GOLD 2023 report, with most of them agreeing with recent updates in definitions, diagnosis, management, and prevention of COPD. The results also highlighted the need to publish GOLD reports in multiple languages and in a shorter, pocket-sized format to increase awareness and adaptation among healthcare providers.

Introduction: The objective of this Delphi study was to understand and assess the level of consensus among respiratory experts on the clinical application of GOLD 2023 recommendations in management of patients with chronic obstructive pulmonary disease (COPD). Methods: The study comprised two online surveys and a participant meeting with 34 respiratory experts from 16 countries. Responses of 73 questions were recorded using a Likert scale ranging from 0 (disagreement) to 9 (agreement). The consensus threshold was 75%. Results: Survey 1 and survey 2 had 34 and 32 participants, respectively; and 25 attended the participant meeting. Consensus was reached on survey 1: 28/42; survey 2: 18/30 close-ended questions. A consensus was reached on the clinical relevance of most updates in definitions and diagnosis of COPD. Mixed results for the treatment recommendations by GOLD were noted: 74% agreed with the recommendation to initiate treatment with dual bronchodilators for group E patients; 63% agreed for including inhaled corticosteroids (ICS)/long-acting β2 agonist(LABA)/ Long-acting muscarinic receptor antagonists (LAMA) as a treatment option for GOLD B patients. Also, consensus lacked on removing ICS + LABA as an initial therapeutic option, in countries with challenges in access to other treatment option;. 88% agreed that they use GOLD recommendations in their daily clinical practice. Conclusions: This Delphi study demonstrated a high level of consensus regarding key concepts of GOLD 2023 report, with most participants favoring recent updates in definitions, diagnosis, management, and prevention of COPD. More evidence on the etiotype based management and treatment options for group B and E are required which could further strengthen clinical application of the GOLD report.
Keywords: Clinical practice; COPD; Delphi procedure; GOLD 2023